KEGAGALAN DEMOKRATISASI DI MESIR PASCA-ARAB SPRING - Samir; M. Hamdan Basyar (Jurnal Penelitian Politik, 2025)
The Arab Spring had a domino effect on Egypt’s political stability. The political transition that occurred after Hosni Mubarak’s resignation from power did not indicate an improving Egyptian democratic climate. The election of Morsi from among civilians to become President democratically did not make the democratic process in Egypt run well. This study aims to analyze the failure of democracy after the Arab Spring and to review the dominance of the military in Egyptian politics. The results of this study indicate that the failure of democracy in Egypt occurred due to the division of the Egyptian political elite which gave birth to polarizing sentiments, the Egyptian economic crisis, and the dominance of the military in Egyptian politics which made it easier for the military to carry out a coup. In this case, the military cannot be separated from its role in national politics because a special order has been formed that strengthens the military domination in Egypt.